The Role of VCP Mutations in the Spectrum of Amyotrophic Lateral Sclerosis—Frontotemporal Dementia - Scarian, Eveljn; Fiamingo, Giuseppe; Diamanti, Luca; Palmieri, Ilaria; Gagliardi, Stella; Pansarasa, Orietta (Frontiers in Neurology, 2022)
Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Dementia (FTD) are two neurological diseases which respectively and primarily affect motor neurons and frontotemporal lobes. Although they can lead to different signs and symptoms, it is now evident that these two pathologies form a continuum and that hallmarks of both diseases can be present within the same person in the so-called ALS-FTD spectrum. Many studies have focused on the genetic overlap of these pathologies and it is now clear that different genes, such as C9orf72, TARDBP, SQSTM1, FUS and p97/VCP can be mutated in both the diseases. VCP was one of the first genes associated with both FTD and ALS representing an early example of gene overlapping. VCP belongs to the type II AAA (ATPases Associated with diverse cellular activities) family and is involved in ubiquitinated proteins degradation, autophagy, lysosomal clearance and mitochondrial quality control. Since its numerous roles, mutations in this gene lead to different pathological features, first and foremost TDP-43 mislocalization. This review aims to outline recent findings on VCP roles and on how its mutations are linked to the neuropathology of ALS and FTD.